Enhancing Website Marketing Through Effective Seo Strategies: A Case Study of Entrefine - Ferdinand, Rico; Permana, Angga Aditya (Unversitas Muhammadiyah Riau, 2024)
The Industrial Revolution 4.0 has influenced consumer behavior, as they use the internet to seek information. This has led to businesses shifting their marketing strategies towards digital marketing. Entrefine sells products such as data management analysis systems and Excel training for corporate employees. One crucial aspect to consider the high number of companies selling similar products, resulting in fierce competition among businesses. The solution to this problem is to design and develop a new website as an information system to offer Excel training services, enhance management efficiency and cost-effectiveness, and implement SEO on the website to improve its search engine rankings, thereby increasing the chances of attracting internet users. The System Development Life Cycle (SDLC) method using the Waterfall model is employed in website development, as it is suitable for systems with low complexity, ensuring well-scheduled and easily controlled project execution. The built system can be deemed successful as the website scored 100% in functionality testing and operates smoothly. The implementation of SEO has proven to be effective, generating a total of 341 traffic and achieving an average ranking of 8.4 within a short period.